2009
DOI: 10.1111/j.1574-6941.2009.00776.x
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal gene transfer and recombination shape mesorhizobial populations in the gene center of  the host plantsAstragalus luteolusandAstragalus ernestiiin Sichuan, China

Abstract: Thirty-three rhizobial strains isolated from the root nodules of Astragalus luteolus and Astragalus ernestii growing on the west plateau at two different altitudes in Sichuan province, China, were characterized by amplified rDNA restriction analysis (ARDRA), amplified fragment length polymorphism (AFLP), and by sequencing of rrs, glnA, glnII and nifH. The ARDRA analysis revealed considerable genomic diversity. In AFLP analysis, 20 of 33 Astragalus rhizobia formed three distinct clades, with others dispersed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 43 publications
(48 reference statements)
1
9
0
1
Order By: Relevance
“…A total of 28 strains were classified as members of the genus Mesorhizobium by using amplified 16S rRNA gene restriction analysis, amplified fragment length polymorphism, BOX element-PCR fingerprinting, 16S rRNA gene sequence analysis and other molecular characterization methods (Li et al, 2009b). The results revealed that the two strains SCAU7 T and SCAU27 exhibited distinct characteristics and differed from the known species of the genus Mesorhizobium.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…A total of 28 strains were classified as members of the genus Mesorhizobium by using amplified 16S rRNA gene restriction analysis, amplified fragment length polymorphism, BOX element-PCR fingerprinting, 16S rRNA gene sequence analysis and other molecular characterization methods (Li et al, 2009b). The results revealed that the two strains SCAU7 T and SCAU27 exhibited distinct characteristics and differed from the known species of the genus Mesorhizobium.…”
mentioning
confidence: 97%
“…Astragalus luteolus and Astragalus ernestii are wild plants that grow at altitudes above 3000 m. Astragalus ernestii grows only in western Sichuan, north-west of Yunnan and in eastern Tibet. Astragalus luteolus is an indigenous endemic plant species grown in western Sichuan province (Li et al, 2009b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the maintenance of heritable phenotypic diversity within host‐associated assemblages, this study considers rhizobia symbiotic with either a native or an invasive legume species across serpentine soil boundaries. Although the rhizobia associated with a given host species may be composed of multiple species, such assemblages are an evolutionarily cohesive unit of microbial biodiversity because they often exhibit high frequencies of horizontal gene transfer, particularly for loci conferring physiological tolerance (Sullivan et al 1995; van Berkum et al 2003; Bailly et al 2007; Lakzian et al 2007; Prosser et al 2007; Li et al 2009; Philippot et al 2010; Sachs et al 2010; Tian et al 2010). The legume Acmispon wrangelianus is native to California and associates with rhizobia in the genus Mesorhizobium (Porter, unpubl.…”
mentioning
confidence: 99%
“…Currently, diverse rhizobia belonging to the genera Rhizobium, Mesorhizobium, Ensifer, and Bradyrhizobium had been isolated from Astragalus spp. grown in different geographic regions in North America, Europe, or Asia [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%